The Depression Conundrum and the Advantages of Uncertainty - Celie, Jan E.; Loeys, Tom; Desmet, Mattias; Verhaeghe, Paul (Frontiers in Psychology, 2017)
According to the WHO (2012), the prevalence of unipolar depressive disorders is rising, even in those places where mental health treatments are widely available. The WHO predicts that these disorders will be the leading contributor to the global burden of disease by 2030. This sobering projection fits poorly with how psychological treatments for depression are presented in the mainstream scientific literature: as highly effective therapies, based upon a sound understanding of the causes of distress. There is a clear discrepancy between the rising prevalence figures on the one hand, and the confident claims of this effectiveness research on the other. This discrepancy prompts a set of complex interlinked questions, which we have called ‘The Depression Conundrum’. In search of a partial answer, the aim of our study was to critically analyse five meta-analytic studies investigating the effectiveness of psychological EBTs for depression, all of which had been published in high impact factor journals. Our examination established a number of methodological and statistical shortcomings in every study. Furthermore, we argue that the meta-analytic technique is founded upon problematic assumptions. The implications of our analysis are clear: decades of quantitative research might not allow us to conclude that psychological EBTs for depression are effective. The uncertainty and questions raised by our findings might act as a catalyst to broaden the way in which depression and associated therapies are researched. In addition, it might contribute toward a more vigorous and interdisciplinary debate about how to tackle this soon-to-be global public health priority number one.